Factors associated with HIV viral suppression among children and adults receiving antiretroviral therapy in Malawi in 2021: Evidence from the Laboratory Management Information System. Issue 7 (14th June 2022) - Ng'ambi, Wingston Felix; Estill, Janne; Jahn, Andreas; Orel, Erol; Chimpandule, Tiwonge; Nyirenda, Rose; Keiser, Olivia
Abstract: Objective: To describe the prevalence of HIV viral suppression and assess the factors associated with HIV viral suppression among persons receiving antiretroviral therapy (ART) in Malawi in 2021. Methods: Implementation study using routinely collected patient‐level HIV RNA‐PCR test result data extracted from the national Laboratory Management Information System (LIMS) database managed by the Department of HIV/AIDS in 2021. We calculated frequencies, proportions and odds ratios (OR) of HIV viral suppression with their associated 95% confidence intervals (95%CIs). We performed a random‐effects logistic regression to determine the risk factors associated with HIV viral suppression among ART patients, controlling for the spatial autocorrelation between districts and adjusting for other variables. Results: We evaluated 515, 797 adults and children receiving ART and having a viral load test in 2021. Of these, 92.8% had HIV viral suppression. ART patients living in urban areas had lower likelihood of HIV viral suppression than those living in rural areas (adjusted OR [aOR] = 0.95, 95%CI: 0.92–0.99, p  = 0.01). There was an increasing trend in HIV viral suppression with increasing ART duration. Routine VL monitoring samples were 39% more likely to have suppressed VL values than confirmatory HIV VL monitoring samples (aOR = 1.39; 95%CI: 1.34–1.43, p  < 0.001). Conclusion: This is the first national analysis of Malawi HIV VL data from LIMS. Our findings show the need to particularly consider the urban residents, those below 20 years, males, those on ART for less than a year as well as those on specific ARV regimens in order to persistently suppress HIV VL and consequently achieve the goal of achieving HIV VL suppression by 2030.